If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(X-4)2+(X-2)2=9
We move all terms to the left:
(X-4)2+(X-2)2-(9)=0
We multiply parentheses
2X+2X-8-4-9=0
We add all the numbers together, and all the variables
4X-21=0
We move all terms containing X to the left, all other terms to the right
4X=21
X=21/4
X=5+1/4
| 3y^2-4y=5 | | 48x-18=36x+46 | | t÷4-2=11 | | (3x+112)=(5x+100) | | 378x=123/5 | | 71/3∙x=1.6÷6/11 | | F(x)=-0.4x^2+9x+1 | | X2+y2=2.25 | | -x+7x+8=0 | | -2=0.8h | | q-18/2=1 | | 110x=2500 | | 3r=54 | | 8x+38=13x-7 | | 2.38x=123/5 | | z-10=5 | | 4f+5=85 | | 0.25p-5=9 | | x+16=4+5x | | 3/4w+6=-15 | | 6(x+2)^2+2+1=0 | | z+9z-6)-2=-10 | | 4=k+4/3 | | 16=e-8 | | 0.6h+11=32 | | 64=e-8 | | 5x+77=13x+45 | | 45-r=24 | | 4m-5m+m+-17=13 | | 9x2=8x-3 | | 12=2(m+3) | | y^2-6y+84=0 |